Total Synthesis of Biologically Active Natural Products Involving Asymmetric Induction Using Chiral Catalysis - Suraksha (My University, 2017)
We have described herein enantioselective approaches for the synthesis of (+)-serinolamide A, (-)-haliclamide, (+)-petromyroxol, (+)-phomonol, (+)-epi-muricatacin and (-)-6-acetoxy-hexadecanolide employed Trost’s DYKAT, MacMillan organocatalyzed aldol reaction, Sharpless AD and Jacobsen’s HKR reactions as key steps.. The merits of these synthetic approaches are high enantio- and diastereoselectivity with high yielding reaction steps. All the new compounds were characterized by 1H-NMR, 13C NMR, HRMS, %ee by chiral HPLC and [α]D25 for all new chiral compounds.
Keywords: Serinolamide A; Haliclamide; Petromyroxol; Phomonol; epi-muricatacin; 6-acetoxy-hexadecanolide